Research on the impact of clean energy demonstration provincial policy on energy poverty: Empirical evidence from China - Yao He; Yue Zhu; Yingying Zhu; Dongri Han (Energy Strategy Reviews)
Energy poverty (hereinafter referred to as EP), as a new type of poverty, is an important challenge affecting energy availability and energy equity, which will lead to multiple deprivation-poverty effects, including economic, social, and ecological. In this paper, a time-varying DID model is used to investigate the impact of China's Clean energy demonstration provincial policy (hereinafter referred to as Clean_policy) on EP from 2008 to 2021. It is found that the Clean_policy significantly reduces EP, a conclusion that still holds after a series of robustness tests. Mechanistic analyses show that the Clean_policy works through two pathways: ''structural adjustment” and ''efficiency improvement.” Heterogeneity analyses show that the Clean_policy is more effective in suppressing EP in areas northwest of the Hu Huanyong Line, in energy-poor areas, and in areas with weak environmental regulations. In addition, further research finds that the Clean_policy can promote the synergy of pollution reduction and carbon reduction (hereinafter referred to as RCP). The findings of this paper provide an important basis for improving the Clean_policy, which is of practical significance for promoting energy equity and sustainable development.